Police science breakthroughs in research and practice
"This book is an authoritative reference source for the latest scholarly material on social problems involving victimization of minorities and police accountability. It also emphasizes key elements of police psychology as it relates to current issues and challenges in law enforcement and police agencies. It covers topics such as police psychology, police brutality, and media coverage"